Digital Aromatherapy Solutions: Leveraging Lemon Scent Technology to Alleviate Nausea and Vomiting in Pregnant Women - Anggraeni, Reni; Wati, Nenden Lesmana; Martin, Neil Madulara; Tio, Lina (International Journal of Nursing Information, 2025)
Nausea and vomiting during pregnancy (NVP) are often perceived as normal conditions, yet they can significantly affect a pregnant woman’s quality of life. With limited use of pharmacological treatments due to concerns for fetal safety, digital innovation has opened new opportunities for non-invasive maternal care. One emerging approach is digital aromatherapy, which combines the convenience of technology with the benefits of natural therapy to help alleviate common pregnancy-related discomforts. This study aimed to evaluate the effectiveness of a lemon-scented digital aromatherapy intervention in reducing symptoms of NVP. A pre-experimental one-group pretest-posttest design was used, involving 100 pregnant women from Indonesia, Philippines and Malaysia. Participants used a mobile-controlled digital diffuser with lemon essential oil for 20 minutes, twice daily, over a period of seven days. The severity of nausea and vomiting was measured using the Pregnancy-Unique Quantification of Emesis and Nausea (PUQE) scale before and after the intervention. The results showed a statistically significant reduction in PUQE scores post-intervention (p < 0.001), indicating a notable decrease in symptom severity. No adverse effects were reported throughout the intervention period. These findings indicate that lemon-based digital aromatherapy is a safe, effective, and accessible complementary approach for managing NVP. This study contributes to the advancement of digital maternal health by introducing a culturally adaptable, user-friendly, and scalable non-pharmacological solution for pregnancy-related symptoms.